Bidirectional relationships between intuitive eating and shape and weight overvaluation, dissatisfaction, preoccupation, and fear of weight gain: A prospective study. (December 2021) - Messer, Mariel; McClure, Zoe; Lee, Sohee; Linardon, Jake
Highlights: Tested bidirectional prospective links between body image facets and intuitive eating. Dissatisfaction was the only facet to predict lower intuitive eating at 3-month follow-up. Intuitive eating predicted low levels of the four body image facets at follow-up. Findings highlight possible intervention targets for promoting intuitive eating. Abstract: Using a prospective design, we investigated possible bi-directional relationships between intuitive eating and four empirically distinct components of negative body image: overvaluation (judgements of self-worth contingent upon weight/shape), dissatisfaction (general discontent with weight/shape), preoccupation (ruminative thinking about weight/shape), and fear of weight gain . We assessed adult women at baseline (T1) and four-month follow-up (T2), as prior work has demonstrated that this time lag is sufficient to detect change in intuitive eating scores. After adjusting for T1 intuitive eating scores and demographic confounds, higher T1 dissatisfaction was the only body image component to significantly predict lower T2 intuitive eating scores in both univariate and multivariate models. Higher T1 intuitive eating scores also significantly predicted lower scores on each of the four negative body image components at T2. Findings suggest that general body discontent may be one of the more important body image variables that lead to decreases in intuitive eating principles. Present findings also add to a growing body of evidence demonstrating the potentially adaptive role of intuitive eating on psychological health indices.